#### Answer

Shania forgot to multiply by the reciprocal fraction when dividing. Once this step is done, she can start cancelling out the factors to find the answer.
$= \frac{(h+5)(h+4)^{2}}{(h+7)(h+2)^{2}} $

#### Work Step by Step

Shania forgot to multiply by the reciprocal fraction when dividing. Once this step is done, she can start cancelling out the factors to find the answer.
$\frac{(h+4)(h-8)}{(h+2)(h+7)} \div \frac{(h-8)(h+2)}{(h+4)(h+5)}$
$= \frac{(h+4)(h-8)}{(h+2)(h+7)} \times \frac{(h+4)(h+5)}{(h-8)(h+2)}$
$= \frac{(h+4)}{(h+2)(h+7)} \times \frac{(h+4)(h+5)}{(h+2)}$
$= \frac{(h+4)(h+4)(h+5)}{(h+2)(h+7)(h+2)} $
$= \frac{(h+5)(h+4)^{2}}{(h+7)(h+2)^{2}} $